The Influence of Brand Ambassador, Product Quality, Brand Image, and Healthy Lifestyle in Purchasing Decisions for Lemonilo X NCT Dream Instant Noodle Products - Syah Abadi Mendrofa (CV. Ulil Albab Corp, 2024)
The purpose of this study is to analyze brand ambassador, product quality, brand image, and healthy lifestyle towards purchasing decisions of lemonilo instant noodle products × NCT Dream in Gunungsitoli city. This research used a quantitative approach. The sample used in this study was 125 respondents using accidental sampling technique in sampling. The data collection technique used in this study was a questionnaire. Data analysis technique using multiple regression analysis. The results of the study show that brand ambassador, product quality, brand image, and healthy lifestyle partially and simultaneously have a positive and significant effect on purchasing decisions of lemonilo instant noodle products × NCT Dream in Gununngsitoli city.